MASALAH ASAS EKONOMI DAN PENYELESAIANNYA MENURUT ISLAM - Ahmad, Shofian (Jurnal Syariah, 2019)
The study aims to compare the basic problems of economy and its solution between modern and Islamic economy. The perception of modern economy is that the conflict between the unlimited needs and limited source caused problem in economy which is clearly rejected by Islam. According to Islam, the problems in economy is caused by human misbehavior i.e. ungrateful to the favors bestowed by Allah, cruelty and crossing the limit stated by Allah. Therefore, the Islamic solution to this problem is to rectify human action who is the key player in the economic activities whether in the field of consumeration, production or distribution